The therapeutic potential of trifluoperazine against ethanol and cold water stress-induced gastric lesions in rat - Mohammad Khoshnoud; Marzieh Rashedinia; Majid Keshavarzi; Amir Hosein Sakhteman; Vida Izadi; Amin Derakhshanfar (Shiraz University of Medical Sciences, 2022)
Gastric erosion is a multifactorial etiological disorder. The study aimed to evaluate the therapeutic effect of trifluoperazine (TFP ) on gastric lesioninduced by cold-water stress and ethanol in rats. TFP 5, 10 and 20 mg/kg as well as pantoprazole (20 mg/kg), as the standard treatment, was administered via oral gavage, 1 h before gastric lesion-induced by 50% ethanol (5 ml/kg per oral) or immersion in cold water (20-22 °C) in rats. Animals were anesthetized 1 h after ethanol gavage or 4 h after immersion in cold water. The stomach tissue was removed and allocated for histopathological and biochemical parameters including malondialdehyde (MDA )level, superoxide dismutase (SOD) and catalase (CAT) activity assay. Both models were induced significant increase in MDA level and decrease in SOD and CAT activity. Pre-treatment with TFP at doses of 10 and 20 mg/kg significantly increased the activity of SOD and CAT enzymes and decreased the concentration of MDA in both models. Also, pre-treatment with TFP ameliorated ethanol and cold-water stress-induced damage. TFP demonstrated gastric mucosal protection against oxidative injuries caused by ethanol and cold-water stress because of its antioxidant properties and inhibition of toxic oxidant in the stomach tissues. Please cite this article as: Mohammad Javad Khoshnoud, Marzieh Rashedinia, Majid Keshavarzi, Amir Hosein Sakhteman, Vida Izadi, Amin Derakhshanfar. The therapeutic potential of trifluoperazine against ethanol and cold water stress-induced gastric lesions in rat. Trends in Pharmaceutical Sciences. 2022;8(1):13-24 .doi: 10.30476/TIPS.2021.92622.1112